Efek Prehabilitation Exercise dengan Resistance Band terhadap Kualitas Hidup Pasien yang Menjalani Total Knee Replacement - Erna Setiawati; Juwita Kusumadewi; Robby Tjandra (Indonesian Journal of Physical Medicine & Rehabilitation, 2020)
ABSTRACT Introduction: An exercise program like prehabilitation exercise is expected to contribute in improving outcomes in Osteoarthritis (OA) postoperatively such as Total Knee Replacement (TKR). Elastic resistance products in prehabilitation exercise programs have been widely used in rehabilitation and are an effective method. Resistance band is one of elastic resistance products that have several advantages. The purpose of this study was to determine the effect of prehabilitation exercise intervention with a resistance band on the quality of life of patients under going TKR using the SF-36 questionnaire. Methods: This study was a randomized controlled trial pre-test and post-test control group design knowing the effects of prehabilitation exercise in patients underwent TKR. 16 subjects were allocated to treatment group (n = 8) which received additional prehabilitation exercise using resistance band and control group (n = 8) with conventional therapy (ergocycle and Transcutaneous Electrical Nerve Stimulation (TENS)) preoperatively. Quality of life assessment using SF-36 score was carried out 4 weeks preoperatively and 8 weeks postoperatively. Results: The mean baseline value of SF-36 in the treatment group is 41.18 ± 9.40 and control group with mean 43.78 ± 5.66, did not differ significantly with p > 0.05. Both groups experienced a significantincrease in their SF-36 post-test scores for the control group (p <0.05) and the treatment group (p <0.05). Comparison between groups showed a significant difference (p <0.05) between the pretest and posttestSF-36 scores where the control group (6.32±3.21) and treatment group (23.95±9.75). Discussion: The SF-36 pre-test score between groups showed no significant d ifference. While the posttest results had significantly increased in SF-36 mean score in both groups. This might be caused byalthough the exercises performed by the two groups were different, they still did exercises that had an effect on joints. Despite of that, treatment group post-test results still had significantly betterimprovement than those of the control group. Conclusion: Prehabilitation exercise intervention using resistance bands improving the quality of life of patients undergoing TKR. The quality of life improving more in those who do prehabilitation exercisethan those who do conventional therapy.Keywords: Prehabilitation exercise, quality of life, total knee replacement.